New Perspectives for Managing Relationships through Psychological Marketing Orientations: Insights and Lessons from a New Psychological Contract. - Godbless, Eromafuru Edward (Archives of Business Research, 2018)
The exigencies of the situation and the increasing dynamics of managing today’s business, and the realizations that today’s customers are the source of competitive advantage, should compel marketers and firms to build bridges across oceans not walls, in order to dig and uncover hidden treasures, missed opportunities and latent wants. The quests to amass wealth and out-perform competitors have led most marketers to put their selfish interests ahead of customers’. This has created spatial gap between the marketing firm, its products and services on one hand and the customer, and his needs, on the other hand. In the new dispensations, marketers must act decisively to redeem their lost image. Over the years the integrity and reputations of most organizations have been hung in the balance due to shoddy and ineffective marketing practices, leading to sub-optimal performance, poor customer retention, and poor service delivery, and negative perception about their true identities. The existing marketing practices that defined relationships in terms of meeting the immediate needs of both marketers and customers based on pre-defined set of rules, have increasingly become inadequate and inconsequential in the emerging turbulent marketing climates. It has therefore become self-evident that the 21st century marketing firms must design strategies and practices that allow them to partner with customers by giving attention to the psychological aspect of the bargain. Evidently, this study portends to be the first of its kind to examine the psychological thrust of building and sustaining relationships with customers in a social contract exchange platform particularly within the context of Sub-Sahara Africa.